The gift of love : Augustine, Jean-Luc Marion, and the Trinity - Staron, Andrew (Minneapolis, Fortress Press, 2017)
The Gift of Love explores the intelligibility of Augustine's claim that we come to know and encounter God in and through our love. Building upon the discoveries of recent scholarship, Andrew Staron reads Augustine's De Trinitate not as presenting the Trinity as a concept to be grasped, but rather as a rational study of the limits of theological language and the possibility of coming to know the Trinity because of those limits. Human dependence on God's initiative indicates that the Trinitarian God of love is knowable only through attention to how God's self-revelation transforms and saves us. Therefore, to see God, one seeks to mark love's formative activity within the heart. Jean-Luc Marion's rigorous description of the gift of love offers to Augustine's theology a phenomenological texture by which the Trinitarian love given in revelation might be made incarnate in one's life. The Gift of Love presents a reason for hope that while coming to know "the Trinity that God is" might be impossible for human beings, it is made possible by God's antecedent gift of love, given in the missions Son and Holy Spirit, and iconically received in the particularity of one's own love. - from publisher.
Part I.A reading of De Trinitate. 1. Language and conversion within the limits of De Trinitate -- 2. Books 1-4 : The revelation of God in salvation history -- 3. Books 5-7 : Naming God -- 4. Books 8-15 : The gift of love to the image of God -- Conclusion to part one -- Part II. Jean-Luc Marion and the question of the unconditioned God. 5. [For]giving theology its groundlessness -- 6. Marking excess : the saturated phenomenon -- 7. The impossible gift -- 8. A love that bears all things --
Revision of the author's thesis (Ph. D.)--Catholic University of America, 2013 under title: Deciphering the gift of love : reading Augustine's De Trinitate through Jean-Luc Marion.
Includes bibliographical references (pages 377-400) and index.
Keywords: Augustine, -- Saint, Bishop of Hippo; Marion, Jean-Luc, -- 1946-; Trinity; Love -- Religious aspects -- Christianity